Canada's Immigration System: Lessons for Europe? - Arthur Sweetman (Intereconomics, 2017)
At a minimum, Canada's observations of immigration policies, practices and outcomes in other countries have broadened and enriched the domestic policy debate, and hopefully other countries will similarly benefit from looking at Canada.
Keywords: 330